(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This paper investigates a streamlined, step-by-step approach to teaching graphic drawing, prioritizing simple yet effective methods to maximize student understanding and skill acquisition. Moving away from overly complex techniques, we propose a pedagogical framework that breaks down the learning process into manageable stages. The study examines the foundational elements of graphic drawing and their gradual introduction, considering visual learning principles, hands-on practice, and effective feedback mechanisms. Through a combination of theoretical insights and practical teaching strategies, this article seeks to equip educators with the tools to deliver engaging and successful graphic drawing courses.